PERANAN MUSYAWARAH GURU PEMBIMBING (MGP) DALAM MENINGKATKAN KOMPETENSI GURU PEMBIMBING SMP KABUPATEN BOYOLALI - Winarno, Agus; Prihartanti, Nanik (Universitas Muhammadiyah Surakarta, 2013)
The purposes of this study are to (1) identify the contribution of teacher advisory association in developing teachers? competence and (2) identify the management implemented for teacher development. This is a qualitative descriptive study. The setting of the study is Junior High School of Boyolali district central Java. The subjects of this study are 80 teacher advisors, 11 Managers, and 8 headmasters. The data are collected through questionnaire, observation, and documentation. The results indicates that the existence of teacher association is needed for teacher advisors as a forum to develop teacher professionalism. Teacher Association has a great contribution to enhance the teachers? competences, including professional, pedagogic, social, and rersonality competence. Various types of counseling skills practiced in this forum. Good management helps improve the professionalism of teachers. In conclusion, teacher association has great contribution to develop the professionalism of teacher advisor. The teachers who are active in this association can develop their competencies and good management of this association gives good results in the teacher development.